The Need of Revision in the Inheritance and Succession Tax - Mehmet GÜNEŞ (International Journal of Public Finance, 2017)
The aim of this study is to explain; Is to raise awareness, even a little bit, by emphasizing that the text of the law which has been practiced in the country for sixty years and which is devoted to all other provisions except death and taxes is far from commercial and social practices. The inheritance and transfer tax, which is a strategic joint venture of the wealthy and the poor, Its place and importance in tax revenues, the positive and benevolent reasons of its existence, and the fiscal and extraordinary purposes of taxation. Along with the impact of globalization, the change in spending-income composition strongly suggests that the preponderance of the taxpayers has increased considerably. How is it that in economic life, economic position, wealth, and wealth are the most important pillars of the three-legged sheet when the economy, economy, and justice, the backbone of the financial life, the indicative of the financial power, and the fallacy are all important, if the economy cannot deny the role of labour, capital, entrepreneurship and natural resources. The fact that income redistribution, elimination of income-wealth inequalities and an important means of intervening in economic life depends on the principle of consolidation of the channels between the taxpayer and the administration as well as the collection of taxable income. In addition, as can be understood from the indicators, if the taxation capacity (political-financial-economic-psychological) is very high and financial socio-economic aspect is taken into consideration; that the share in the budget can be increased without any reaction to the taxpayer. The data used were obtained from the official sites of the General Directorate of Budget and Financial Control and the Revenue Administration. Provisions containing practical and theoretical conflicts have been identified and proposed as solutions for the tax complexity index being too high. The conceptual framework of the study, the critique, and defense of its existence in the study has been explored historically, and the forms of practice have been explained. Limited work and financial legislation in the acute meaning of these issues, which have to be resolved and forgotten as soon as possible, have been studied.